Different types of variability in tennis practice - Davis-Higuera, M. (Coaching and Sport Science Review, 2018)
Variability is a term that is gaining traction in the tennis coaching world; traditional approaches which emphasise either a oneapproach- fits-all `text`-book` model of instruction are being abandoned as a result of the acknowledgement that people have differences and the acknowledgement that even the top players show variability. This article summarises some of the different types of variability that might occur in tennis practice, and gives recommendations for coaches.